The Internet in the Workplace: How New Technology Is Transforming WorkThe Internet in the Workplace: How New Technology Is Transforming Work, by Wallace Patricia. Cambridge: Cambridge University Press, 2004. - Desouza, Kevin C. (Academy of Management Review, 2005)
The article reviews the book ?The Internet in the Workplace: How New Technology is Transforming Work,? by Patricia Wallace.